Evaluation of automated cell disruptor methods for oomycetous and ascomycetous model organisms - Takao Kasuga; Mai Q. N. Bui (Fungal Genetics Reports, 2011)
Two automated cell disruptor-based methods for RNA extraction, disruption of thawed cells submerged in TRIzol Reagent (method QP), and direct disruption of frozen cells on dry ice (method CP), were optimized for a model oomycete, Phytophthora capsici, and a model filamentous ascomycete, Neurospora crassa. The results were compared with more conventional methods of manual grinding in a mortar and pestle under liquid nitrogen (method M&P) and those using lyophilized samples. A chip-based electrophoresis system showed that methods CP and M&P yielded high integrity RNA from both P. capsici and N. crassa. In contrast, method QP and lyophilized sample-based methods resulted in inconsistent RNA integrity between the two organisms, indicating they are not safe alternatives for method M&P. Microarray mRNA profiling for P. capsici revealed alterations in global mRNA profiles in those samples that the chip-based electrophoresis detected slight decreases in RNA integrity. Despite this, RNA integrity of these samples could still be high enough to pass conventional stringent quality control measures. This demonstrated the necessity of global mRNA profiling for the evaluation of RNA extraction protocols.